Coronavirus disease 2019 and extra-pulmonary tuberculosis co-infection – A case report and review of literature. (February 2021) - Gerstein, Shawn; Khatri, Akshay; Roth, Nitzan; Wallach, Frances
Abstract: The Coronavirus disease 2019 (COVID-19) pandemic continues to cause significant global morbidity and mortality, leading to the need to study the course of the disease in different clinical circumstances and patient populations. While co-infection between COVID-19 and many pathogens has been reported, there has been limited published research regarding co-infection with Mycobacterium tuberculosis . We describe a case of co-infection involving COVID-19 and extra-pulmonary tuberculosis in a patient with cirrhosis, and review the current literature regarding COVID-19 and tuberculosis co-infection. In spite of several co-morbidities that have been shown to portend a poor prognosis in patients with COVID-19 infection, our patient fully recovered.